2016
DOI: 10.1093/ckj/sfw026
|View full text |Cite
|
Sign up to set email alerts
|

Haematological malignancies and acute kidney injury requiring nephrology consultation: challenging the worst of the worst

Abstract: BackgroundAcute kidney injury (AKI) often complicates the course of haematological malignancies (HMs) and confers a worse prognosis. The majority of these patients are managed by the attending physician, yet, a small group, mostly coincident with the worst presentation and outcomes, requires nephrology consultation, challenging the clinician with ethical issues regarding the decision to initiate or forgo renal support therapy. The purpose of this work is to identify the prognostic determinants for in-hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…24 We identified that 10% of patients used ARRT near death. Although the diagnosis of HM by itself is not a reason to withhold ARRT, 25 hemodialysis is associated with increased health-care costs, longer length of stays, 11 (16) 16 (18) .16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We identified that 10% of patients used ARRT near death. Although the diagnosis of HM by itself is not a reason to withhold ARRT, 25 hemodialysis is associated with increased health-care costs, longer length of stays, 11 (16) 16 (18) .16…”
Section: Discussionmentioning
confidence: 99%
“…24 We identified that 10% of patients used ARRT near death. Although the diagnosis of HM by itself is not a reason to withhold ARRT, 25 hemodialysis is associated with increased health-care costs, longer length of stays, aggressiveness of care, and late palliative care enrollment, especially in patients with multiple myeloma. 26,27 Our findings highlight the importance of advanced care planning documentation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Portugal, the objective was to identify the prognostic determinants of in-hospital mortality of patients with hematological malignancies. The study concluded that the association of mechanical ventilation, septic shock, and allogeneic stem cell treatment was identified as an independent predictor of death in patients with hematological diseases and AKI, with only a small chance of survival if all three were present (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of all three conveyed an 86% probability of in-hospital death. 14 Multiple myeloma (MM), in particular, has the highest 5-year AKI incidence rate among all malignancies. 8 On presentation, up to 50% of patients will already have kidney involvement, 15 which is associated with higher mortality.…”
Section: Malignancy Typementioning
confidence: 99%